A Mathematical Model for Identifying Truth in Observations Made within Individual Human Self-Awareness - Williams, Andy (My University, 2020)
A large body of work purports to identify the functions of the human system through observations that can be validated within human self-awareness. That is, using observations that can be made in the human self-awareness to validate what in this paper are called human-centric models of the functionality of the human system, or human-centric functional models. This body of work, accumulated over thousands of years, has been largely inaccessible to the scientific study of consciousness and other functions because it's written in terms that require a very different training, which is training in observing one's self-awareness. Making scientific or mathematical use of observations made within human self-awareness is a challenge. What can be observed to be true in one's self-awareness, and what can be proved true mathematically, have so far been two different things. Representing an experiment as a channel through which information representing truth can be transmitted, this paper explores the use of Information Theory to gauge the capacity of an experiment in self-awareness to identify a truth, such as determining the validity of any given function defined by a functional model for consciousness. In providing this mechanism to prove that an awareness exists and that it reflects truth, this paper attempts to make the entire set of observations made using human self-awareness accessible to mathematicians and scientists.
Keywords: Functional Modeling Framework; Information Theory; Integrated Information Theory